Sistem Informasi, Organisasi, dan Strategi: Studi Litratur Permasalahan Manajemen Pada Teknologi Informasi - Novri Wulandari Wulan (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2022)
In the increasingly rapid development of technology and information that has changed the market to become competitive, in carrying out company operations today, companies create very detailed information systems regarding all operational and financial activities so that they can be used at any time to create reports that can be used to make decisions by management to manage company resources effectively and efficiently. Organizational structure and company culture can influence the acceptance and adaptation of information technology. User engagement, culture change, and change management are important aspects for understanding how organizations can optimize IT implementation. Further research is needed to identify how big a role information systems play in business development and how companies use information systems.